Relating small waterbody denitrification with ecosystem respiration in an intensive anthropogenic region - Xuemei Zhao; Yi Zhu; Xu Yang; Li Zhang; Xuan Huang; Chunwang Li; Kebing Chen; Han Lin; Dongli She; Yongqiu Xia (Journal of Hydrology, 2025)

Genetic Diversity and Genetic Structure among Four Selected Strains of Whiteleg Shrimp (Litopenaeus vannamei) Using SSR Markers - Zhe Zhang; Chengkuan Lu; Kebing Lin; Weiwei You; Zhangwu Yang (Fishes, 2023)
The whiteleg shrimp (Litopenaeus vannamei) is one of the most economically important aquaculture species in China. Genetic diversity is crucial for maintaining the gene pool of farmed shrimp. In this study, the effects of artificial selection on the genetic structure of four whiteleg shrimp strains were evaluated using microsatellite sequences. The results showed that the observed heterozygosity (Ho), expected heterozygosity (He), and the polymorphism information content (PIC) of the four selected strains ranged from 0.446 to 0.574, 0.450 to 0.566, and 0.435 to 0.509, respectively. All the selected strains maintained a moderate level of genetic diversity. Most inbreeding coefficients (Fis) in the four strains were positive but not significantly different from zero, indicating a relatively low degree of inbreeding within each strain. However, He and PIC in line 5 showed a decreasing trend from the 2017 to the 2019 generations, and Fis in line 10 showed a significant increasing trend across generations, indicating that measures must be taken to maintain the level of genetic diversity for lines 5 and 10. UPGMA cluster trees showed that the four breeding lines had apparent genetic differences, which could provide a genetic basis for studying crossbreeding between selective lines and the utilization of heterosis. This study will be useful for population genetic research and the breeding strategies of whiteleg shrimp.

Liver proteomic analysis of the large yellow croaker (Pseudosciaena crocea) following polyriboinosinic:polyribocytidylic acid induction - Yinnan Mu; Xiang Wan; Kebing Lin; Jingqun Ao; Xinhua Chen (Fish Physiology and Biochemistry, 2013)

Diagnosis of nervous necrosis virus in orange-spotted grouper, Epinephelus coioides, by a rapid and convenient RT-PCR method - Yinnan Mu; Kebing Lin; Xinhua Chen; Jingqun Ao (Acta Oceanologica Sinica, 2013)